Sobre o operador de fecho, um conceito que permeia muitos e distintos tópicos matemáticos - de Araujo Feitosa, Hércules; Golzio, Ana Claudia; Soares, Marcelo Reicher (INTERMATHS, 2022)
We present the closure operators and detach several distinct topics of mathematics in which we can observe the action of these closure operators. So, we can see these operators as a trans-topic concept. Considering that these mathematics theories can be applied to so many fields, then we enhance the closure operators as a transdisciplinary notion.